Application of the Health Belief Model to Antihypertensive Medication Adherence: A Meta-Analysis - Widiyanto, Aris (GLOBAL HEALTH SCIENCE GROUP, 2023)
This study explores several Health Belief Model (HBM) components, such as perceived susceptibility, severity, benefit, barriers, and cues to action. Through the rigorous conduct of a comprehensive systematic review followed by a meticulous meta-analysis, this research intends to determine the impact of HBM constructs on anti-hypertensive medication adherence in hypertensive patients. Nineteen papers in total were chosen for the comprehensive review and analysis in this research, which employed the following PICO elements as Population- those suffering from elevated blood pressure; Intervention - strong Perception of benefits, presence of cues to action, and perceptions of vulnerability; Comparison – week perception of benefits, absence of cues to action, and no perception of vulnerability; Outcome - medication adherence. Data were collected from various databases, including PubMed, Springer Link, Science Direct, and Google Scholar. Meanwhile, data analysis was conducted using RevMan 5.3. 19 articles (2012-2020) Adherence to Hypertensive Medication among Hypertensive Patients with Cross-Sectional Design. The 19 articles included in this study design utilized a cross-sectional study design. The results demonstrated that a strong perception of benefit (aOR= 1.63; 95% CI= 1.05 to 2.52; p= 0.030), cues to action (aOR= 1.63; 95% CI= 1.05 to 2.52; p= 0.030), and perceived vulnerability (aOR= 2.16; CI 95% = 1.59 to 2.93; p< 0.001) were statistically significant factors in increasing medication adherence among hypertensive patients. This study investigates the impact of HBM components, such as perceived benefits and cues of action, on hypertensive medication adherence across various populations, including Vietnam, Taiwan, China, Ethiopia, Egypt, and Ghana.